A Review of Cyberbullying and Cybervictimization: Taxonomy, Challenges, Limitations, and Recommendations for Future Researchers - Ades, Andaleep Sadi (Mediterranean Journal of Social Sciences, 2021)
Cyberbullying and cybervictimization is vital and recent issue that still require further investigations. It is classified as a global problem, serious risk and danger that challenging researchers in term of assessment, nature and measuring that demand massive effort to limit and reduce its prevalence and consequences. The aim of the study is to underline challenges, limitations, and recommendations that related to cyberbullying and cybervictimization that need to be explored and investigated in greater depth in future researches. The current study intends to analyse the twenty- seven previous studies and build taxonomy that highlights gabs and shortage of the phenomena into four main sections: research, programs, methodology and theories and model. Based on researcher analysis there are four main sections that present the challenges and limitations, whereas eleven sub-sections and eight divisions give more details about these challenges and limitations. Discussion: The result of the review present that more factors need to integrate and re-investigate whereas theories need to link, and methodology aspects require to develop. In addition, new aspects and open areas that demand investigate in future. This review and taxonomy provide a unique opportunity to develop and create additional research fields. Received: 8 March 2021 / Accepted: 20 April 2021 / Published: 17 May 2021